Sargassum blooms in the East China Sea and Yellow Sea: formation and management - Zhuang, M.; Liu, J.; Ding, X.; He, J.; Zhao, S.; Wu, L.; He, P.
Large-scale Sargassum blooms, known as golden tides, have been occurring along the coast of the Yellow Sea in recent years, resulting in an enormous loss of Pyropia yezoensis production. To locate the source of the blooms, we performed large-scale spatio-temporal sampling in the South Yellow Sea, East China Sea, and Jeju Island, South Korea. Based on morphology and molecular traits, the attached and floating Sargassum samples collected from the three regions were all identified as Sargassum horneri, although slight differences were observed in morphology among samples. Genetic distance and automatic barcode gap discovery analysis revealed very low genetic diversity among the three regions. The 33 samples from 12 sites were divided into six haplotypes, and the samples from the ECS shared more haplotypes than samples from other two regions. Our results suggested that S. horneri in the ECS was responsible for the formation of blooms in the Yellow Sea.
Keywords: MACROALGAL BLOOMS; ORIGIN; SARGASSUM HORNERI; AQUACULTURE; YELLOW SEA